Bacon's The Advancement of Learning: A Possible Influence on Jonson's The Alchemist. Issue 1 (23rd December 2020) - Lin, Qin
Abstract: Although sources for parts of the plot of Ben Jonson's The Alchemist, particular scenes, specific speeches, and its use of the language of alchemy have been suggested, critics have ignored the connections between the play and Francis Bacon's The Advancement of Learning . This article argues that Jonson's dramatization of astrology, magic, and alchemy in The Alchemist is probably informed by Bacon's ideas about the three distempers of learning in his The Advancement of Learning .